2023
DOI: 10.1038/s41598-023-38941-w
|View full text |Cite
|
Sign up to set email alerts
|

Water and oil-grease barrier properties of PVA/CNF/MBP/AKD composite coating on paper

Abstract: In this paper, three kinds of micro-nano bamboo powder (MBP) and alkyl ketene dimer (AKD) were added to the polyvinyl alcohol/cellulose nanofiber (PVA/CNF) coating to prepare PVA/CNF/MBP coated paper and PVA/CNF/M-MBP/AKD coated paper. The results showed that MBP improved the oleophobicity of PVA/CNF coating, and the grease resistance grade of PVA/CNF/B-MBP and PVA/CNF/M-MBP coated papers reached the highest level, with a kit number of 12. Among the PVA/CNF/MBP coated papers, the PVA/CNF/M-MBP coated paper has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, the resulting film is brittle in a dry state, resulting in a slight decrease in the tear strength. On the other hand, the hydrophobic groups of AKD exist on the fibres' surfaces, forming a thin film that blocks direct contact between the fibres and the water [69]. In this experiment, it was found that the film formed by the AKD coating's wet state has a certain degree of toughness.…”
Section: Mechanical Properties Of the Akd-coated Paper Mulchmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the resulting film is brittle in a dry state, resulting in a slight decrease in the tear strength. On the other hand, the hydrophobic groups of AKD exist on the fibres' surfaces, forming a thin film that blocks direct contact between the fibres and the water [69]. In this experiment, it was found that the film formed by the AKD coating's wet state has a certain degree of toughness.…”
Section: Mechanical Properties Of the Akd-coated Paper Mulchmentioning
confidence: 84%
“…At the same time, the wet mechanical strength is significantly enhanced. This is because the AKD molecules contain hydrophobic and reactive groups, which react with the carbonyl groups of fibres to form covalent bonds [66][67][68], creating a stable film on the fibres' surfaces [69]. It further binds the fibres on the surface of the paper mulch, enhancing the comprehensive force among the fibres and increasing the tensile strength.…”
Section: Mechanical Properties Of the Akd-coated Paper Mulchmentioning
confidence: 99%
“…It can be applied by a variety of methods, including gravure roller (forward, reverse and offset, flex), return roller, air knife or Mayer bar. Polyvinyl alcohol (PVA) is a suitable coating carrier with good film-forming and biodegradable properties [29]. Additionally, one of the most important factors affecting the barrier properties of coated paper is the coating grammage.…”
Section: Discussionmentioning
confidence: 99%
“…Water absorption of paper was determined using Cobb Absorption Tester according to GB/T 1540 standard. 48 The WCA was measured using a Kruss DSA10 optical contact angle system. A drop of DI Water (roughly 5 μL) through a rotary knob was manually dispensed on the surface of a sample to acquire the WCA at five different sites on each one.…”
Section: Characterizationmentioning
confidence: 99%